Roles and Challenges of Traditional Birth Attendants in Maternal Healthcare Delivery in Awka South Local Government Area, Anambra State - Ngozi Chinenye Okeke (RESEARCH JOURNAL OF HUMANITIES AND CULTURAL STUDIES, 2026)
The study explored the role and the problems of Traditional Birth Attendant (TBA) in maternal health care in Awka South Local Government of Anambra State, Nigeria. The study utilized mixed methods research that combined quantitative and qualitative methods based on the Health Belief Model to explore factors that impact on health seeking behaviour including perceptions, cultural norms, and perceived control. A sample of 204 respondents were selected using a multistage sampling procedure and key informants were interviewed in-depth. A structured questionnaire and interview guide were used to gather data. The data obtained were analysed descriptively using frequencies and percentages for quantitative data, and thematically for qualitative data. It was found that TBAs have important functions in antenatal care, delivery assistance, postnatal support, health education, emotional counselling and referral of complicated cases. But there are several issues that stop them from doing so: their lack of formal training, they are not well equipped with medical items, they are not well integrated in the health system, they are financially constrained, and they are not well connected to emergency referral services, and cultural expectations and reliance on traditional practices are also constraining the uptake of modern health procedures. Yet, despite these obstacles, many TBAs were willing to be trained and work with experienced health care providers. The study therefore recommended the integration of TBAs in the formal health system through structured training programme, provision of basic medical supplies, improvement of referrals, regular supervision, supportive policy and strengthening of community partnership and public health education due to their expected positive impacts on maternal health outcomes, reduction of preventable childbirth complications and enhancement of maternal health services delivery in Awka South LGA and similar.